2018
DOI: 10.1002/advs.201700491
|View full text |Cite
|
Sign up to set email alerts
|

2D Black Phosphorus: from Preparation to Applications for Electrochemical Energy Storage

Abstract: Black phosphorus (BP) is rediscovered as a 2D layered material. Since its first isolation in 2014, 2D BP has triggered tremendous interest in the fields of condensed matter physics, chemistry, and materials science. Given its unique puckered monolayer geometry, 2D BP displays many unprecedented properties and is being explored for use in numerous applications. The flexibility, large surface area, and good electric conductivity of 2D BP make it a promising electrode material for electrochemical energy storage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
145
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 218 publications
(315 reference statements)
0
145
0
2
Order By: Relevance
“…In the past few years, there are many articles that have reported the practical application of BP in batteries, photodetectors, sensors, field‐effect transistors, and solar cells, and these applications have been summarized in some reviews . Meanwhile, many papers have reported the application of photocatalysis field, while there is no article that has detailedly reported that BP as a photocatalyst is employed in various aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, there are many articles that have reported the practical application of BP in batteries, photodetectors, sensors, field‐effect transistors, and solar cells, and these applications have been summarized in some reviews . Meanwhile, many papers have reported the application of photocatalysis field, while there is no article that has detailedly reported that BP as a photocatalyst is employed in various aspects.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] Recently, binary metal-free heterostructures combining BP and CN have shown promise in photocatalytic H 2 evolution and reactive oxygen species generation. [2][3][4][5][6][7][8][9][10][11] Owing to the unique optical and electrical properties, BP holds large promise in the fields of energy and catalysis. The preparation of these materials relies on the growth and exfoliation of BP crystals and the production cost and complexity increase inevitably.…”
mentioning
confidence: 99%
“…Compared with bulk battery materials, 2D nanosheets (e. g., TiO 2 , V 2 O 5 , MoS 2 ) with ultrathin thickness and high surface-to-volume ratio usually exhibit boosted pseudocapacitive behavior resulting from the more exposed active sites, decreased diffusion barrier and distance of electrolyte ion, and alleviated volumetric strain. Since the application of 2D materials for LICs is still in the early stage, other newly developed 2D materials (e. g., phosphorene, [95] graphdiyne, [96] metal thiophosphate, [97] and layered double hydroxide nanosheets [98] ) also deserve to be investigated, and new 2D materials should be incessantly exploited to achieve high-performance LICs. Also, assembling 2D nanosheets into 3D porous architectures can improve the contact/interaction with electrolyte and facilitate the surface-driven pseudocapacitive charge storage.…”
Section: Discussionmentioning
confidence: 99%